Catʼs Claw Oxindole Alkaloid Isomerization Induced by Cell Incubation and Cytotoxic Activity against T24 and RT4 Human Bladder Cancer Cell Lines - Kaiser, Samuel; Dietrich, Fabrícia; Resende, Pedro Ernesto de; Verza, Simone Gasparin; Moraes, Renata Cougo; Morrone, Fernanda Bueno; Batastini, Ana Maria Oliveira; Ortega, George González (Planta Medica, 2013)
The antitumor activity of Uncaria tomentosa, a native vine from the Amazonian rainforest, has been ascribed to pentacyclic oxindole alkaloids occurring in its bark. Former studies have shown that this activity, as well as its intensity, depends on whether catʼs claw alkaloids occur as original compounds or isomerized derivatives. This work addresses this aspect, using T24 and RT4 human bladder cancer cell lines for that purpose. Bark samples were extracted by dynamic maceration, prepurified with cross-linked polyvinylpyrrolidone and properly fractioned by an ion exchange process to obtain an oxindole alkaloid purified fraction. Alkaloid isomerization was induced by heating it under reflux at 85 °C. Samples collected after 5, 15, and 45 min of heating were analyzed by HPLC-PDA, freeze-dried at once, and separately assayed using the non-isomerized purified fraction for comparison purposes. The latter showed significant and dose-dependent cytotoxic activity against both T24 and RT4 cancer cell lines (IC50: 164.13 and 137.23 µg/mL, respectively). However, results for both cell lines were equivalent to those observed for isomerized samples (p > 0.05). The alkaloid isomerization induced by the incubation conditions (buffered medium pH 7.4 and temperature 37 °C) helps to explain the similar results obtained from non-isomerized and isomerized samples. Mitraphylline, speciophylline, uncarine F, and, to a lesser degree, pteropodine were more susceptible to isomerization under the incubation conditions. Thus, the alkaloid profile of all fractions and their cytotoxic activities against T24 and RT4 human bladder cancer cell lines are determined to a large extent by the incubation conditions.
Keywords: Uncaria tomentosa; Rubiaceae; oxindole alkaloids; isomerization; incubation conditions; cytotoxic activity; T24 and RT4 human bladder cancer cell lines